2019
DOI: 10.1002/smi.2862
|View full text |Cite
|
Sign up to set email alerts
|

Initial validation of the dyadic coping inventory for financial stress

Abstract: Financial stress can have a detrimental impact on a couple's relationship but there is no validated instrument to assess the way couples cope with financial stress. This study sought to validate the Dyadic Coping Inventory for Financial Strain (DCIFS), an adaptation of the Dyadic Coping Inventory to financial stressors, with self-report data collected from 132 heterosexual couples seeking couple and/or family therapy services. Confirmatory Factor Analysis results supported a 23-item version consisting of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…Of the 66 possible correlations among subscales in participants in same-gender couples, 61 were statistically significant in a direction consistent with past versions of the DCI (Falconier et al, 2019; Randall et al, 2016) (see Table 4). In participants in different-gender couples, 65 of the 66 possible correlations among subscales were statistically significant in a direction consistent with expectations.…”
Section: Resultssupporting
confidence: 57%
See 4 more Smart Citations
“…Of the 66 possible correlations among subscales in participants in same-gender couples, 61 were statistically significant in a direction consistent with past versions of the DCI (Falconier et al, 2019; Randall et al, 2016) (see Table 4). In participants in different-gender couples, 65 of the 66 possible correlations among subscales were statistically significant in a direction consistent with expectations.…”
Section: Resultssupporting
confidence: 57%
“…Lastly, a model was fit to confirm the overall 11-factor structure for the DCI-SMS: (a) stress communication in self and (b) partner, (c) emotion-focused supportive DC in self and (d) partner, (e) problem-focused supportive DC in self and (f) partner, (g) negative DC in self and (h) partner, (i) emotion-focused common DC, (j) problem-focused DC, and (k) evaluation of DC. For each model, latent factors were allowed to freely covary given other studies which found strong covariation among DCI latent factors (Falconier et al, 2019; Randall et al, 2016). All analyses were conducted in RStudio Version 1.3.959 (RStudio Team, 2020) with R version 4.1.3 (R Core Team, 2022) using the cfa function from the lavaan package (Rosseel, 2012).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations